Treatment of Gravitational Pulling Sensation in Patients With Mal de Debarquement Syndrome (MdDS): A Model-Based Approach - Yakushin, Sergei B.; Raphan, Theodore; Cho, Catherine (Frontiers in Integrative Neuroscience, 2022)
Perception of the spatial vertical is important for maintaining and stabilizing vertical posture during body motion. The velocity storage pathway of vestibulo-ocular reflex (VOR), which integrates vestibular, optokinetic, and proprioception in the vestibular nuclei vestibular-only (VO) neurons, has spatio-temporal properties that are defined by eigenvalues and eigenvectors of its system matrix. The yaw, pitch and roll eigenvectors are normally aligned with the spatial vertical and corresponding head axes. Misalignment of the roll eigenvector with the head axes was hypothesized to be an important contributor to the oscillating vertigo during MdDS. Based on this, a treatment protocol was developed using simultaneous horizontal opto-kinetic stimulation and head roll (OKS-VOR). This protocol was not effective in alleviating the MdDS pulling sensations. A model was developed, which shows how maladaptation of the yaw eigenvector relative to the head yaw, either forward, back, or side down, could be responsible for the pulling sensation that subjects experience. The model predicted the sometimes counter-intuitive OKS directions that would be most effective in re-adapting the yaw eigenvector to alleviate the pulling sensation in MdDS. Model predictions were consistent with the treatment of 50 patients with a gravitational pulling sensation as the dominant feature. Overall, pulling symptoms in 72% of patients were immediately alleviated after the treatment and lasted for 3 years after the treatment in 58% of patients. The treatment also alleviated the pulling sensation in patients where pulling was not the dominant feature. Thus, the OKS method has a long-lasting effect comparable to that of OKS-VOR readaptation. The study elucidates how the spatio-temporal organization of velocity storage stabilizes upright posture and how maladaptation of the yaw eigenvector generates MdDS pulling sensations. Thus, this study introduces a new way to treat gravitational pull which could be used alone or in combination with previously proposed VOR readaptation techniques.